Micro-PIV and CFD studies show non-uniform wall shear stress distributions over endothelial cells - Dol, Sharul sham; Salek, M.; Viegas, K.; Rinker, K.; Martinuzzi, R. (2010)
Wall shear stress acting on arterial walls is an important hemodynamic force determining vessel health. A parallel-plate flow chamber with a 127 µm-thick flow channel is used as an in vitro system to study the fluid mechanics environment. It is essential to know how well this flow chamber performs in emulating physiologic flow regimes especially when cultured cells are present. Hence, the objectives of this work are to computationally and experimentally study the characteristic of the flow chamber in providing a defined flow regime and shear stress to cultured cells and to map wall shear stress distributions in the presence of an endothelial cell layer. Experiments and modeling were performed for the nominal wall shear stresses of 2 and 10 dyn/cm2. Without endothelial cells, the flow field is uniform over 95% of the chamber cross-section and the surfaces are exposed to the target stress level. Using PIV velocity data, the endothelial cell surfaces were re-constructed and flow over these surfaces was then simulated via FLUENT. Once endothelial cells are introduced, local shear variations are large and the velocity profiles are no longer uniform. Due to the velocity distribution between peaks and valleys, the local wall shear stresses range between 47-164% of the nominal values. This study demonstrates the non-uniform shear stress distribution over the cells is non-negligible especially in small vessels or where blockage is important. Copyright © 2010 by ASME.